Flexible, Front-Facing Luminescent Solar Concentrators Fabricated from Lumogen F Red 305 and Polydimethylsiloxane - Ian A. Carbone; Katelynn R. Frawley; Melissa K. McCann (International Journal of Photoenergy)
Luminescent solar concentrators (LSCs) fabricated with transparent host materials and fluorescent organic dyes are cost effective and versatile tools for solar power production. In this study, the first flexible, front-facing LSCs utilizing Lumogen F Red 305 (LR305) and polydimethylsiloxane (PDMS) were demonstrated. Bulk-doped devices, fabricated with dye evenly distributed throughout the waveguide, were optimized for light gain with LR305 concentrations between 0.075 and 0.175 g/l. Thin-film devices, fabricated with a thin layer of luminescent material applied to the bottom side of the waveguide, were optimized between 0.5 and 0.75 g/l. The bulk-doped and thin-film devices produced light gains of 1.86 and 1.89, respectively, demonstrating that flexible designs can be developed without sacrificing power production. Bulk-doped devices proved to be less effective than thin-film devices at collecting direct light due to the placement of fluorescent dyes above the front-facing solar cell. Thin-film devices demonstrated less light collection than bulk-doped devices further from the device centers possibly due to quenching and self-absorption losses at higher dye concentrations. Light collection was minimally impacted by moderate bending in both LSC designs, suggesting that flexible, front-facing devices could be effectively deployed on curved and uneven surfaces. Finally, optical measurements of the LSC waveguides suggest that they could support plant growth underneath. Similar designs could be developed for applications in agricultural settings.